O curso de licenciatura em Pedagogia/PARFOR - Plano Nacional de Formação de Professores para a Educação Básica: implicações na prática pedagógica dos alunos-professores, do polo de Imperatriz MA - Pereira, Maria Elinete Gonçalves (2016)
The research entitled “License in Pedagogy Course/ PARFOR – National Plan for Elementary Teacher Education: implications in the practice of student-teachers in Imperatriz – MA”, aimed primarily at analyzing the implications of the License in Pedagogy / PARFOR in the teaching practices of student-teachers. It focuses on the perception that they have about their education and if it led them to different teaching practices. As basis for this investigation, we used Saviani’s book (2013), “Pedagogia histórico-crítica”, understanding that the school, through mediators of the teaching and learning process, can and should develop a critical and pedagogical practice that will be able to transform society. The theoretical reference developed from two axel points: 1 – teacher education from the 90s, embracing the curricular guidelines for the elementary teacher trainings, the curricular guidelines of the License in Pedagogy courses, the theoretical contributions about initial training, curriculum and teaching education; 2 – pedagogy practice among teachers, focusing on the concept of teaching practices and the relation between theory and practice, critical and historical pedagogy: an alternative to the construction of a transforming pedagogical practice, didactics and critical and historical pedagogy: a possible reality. We used the contributions of Pimenta (1997), Brzezinski (2002), Gatti (2010; 2011), Barreto (2010), Ramalho, Nunez e Gauthier (2004) Bissolli da Silva (1999), Frigotto (2000), Silva (2007), Pacheco (2005), Arroyo (2013), Kosik (1976), Freire (2014), Vázquez (2007), Saviani (2009; 2011; 2012; 2013), Veiga (2013), Libâneo (1985; 1990; 2003), Caldeira (2010), Gasparin (2012), Bourdieu (2008), Gauthier (2013), Gadotti (1999), among others. The investigation adopted a qualitative perspective related to teaching conceptions, values, understandings, meanings, interpretations and attitudes, situated in the historical and social process, to bring possible transformations to reality. To collect dada, we developed procedures as an identity profile questionnaire, semi-structured interviews and document inquiry. The dada were analyzed and organized by using content analysis techniques, from Bardin (2011) and Franco Barbosa (2003). The research population was the Pedagogy/PARFOR student-teachers from the area of Imperatriz – MA. The research noticed that the step-bystep routine of these student-teachers was inherited from the traditional school: responding to official curriculum demands; teaching and class planning; schedule; pedagogical meetings; etc. However, we highlight that these relations are better perceived when observing students difficulties, social practice appreciation, even if the context is totally open to a critical proposition for the teaching and learning process.